Planning for Normalization of the Apu River in the Post-Mining Area - Gunawan, Risal; Ernawati, Rika; Cahyadi, Tedy Agung (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2024)
Miners often leave traces such as irregular river channels, holes in the mining area without repair measures, the mining area is located in Boyolali Regency, precisely in the Apu River area. Apu River is one of the centers of Merapi sand mining which is quite large, mining activities have the potential to cause river overflows. For this reason, improvements need to be made. This study aims to plan a post-mining model in a river that has changed, the method in this study is to take water discharge directly with 5 sampling points and analyze the distribution of gumbell rainfall for 10 years and make a comparison, then a trapezoidal open channel plan is made and modeled in HEC-RAS software. Based on the results of taking river water discharge, it is known that the maximum river flow velocity is 0.57 m3/second, while the results of the rainfall analysis are 2.77m3/second. so that in repairing the cross-section using a higher water discharge. The method of repairing the river cross-section is the trapezoidal open channel method, the dimensions of the open channel are designed using a manning roughness of 0.30. The initial design depth of the channel was 1.35 m plus 0.60 m to avoid flood overflow, so that the channel depth became 1.95 m.